Struktur Penyajian Dikia Pauah Pada Masyarakat Nagari Sungai Sapih Kecamatan Kuranji Kota Padang - Mutia Yamesty; Marzam Marzam (FBS Universitas Negeri Padang, 2022)
This research aims to reveal and describe the Structure of Peyajian Dikia Pauah in Nagari Sungai Sapih Community Kuranji District, Padang City. This type of research is qualitative research using descriptive methods. This research instrument is the researcher himself and assisted with supporting instruments such as stationery, flashdisk, and mobile phone. The data type uses primary data and secondary data. Data collection techniques are conducted utilizing observation, interviews, and documentation. The steps of analyzing data are collecting data, describing data, and concluding data. The results showed that the presentation structure of dikia was done at the time after Isha to dawn because the Prophet Muhammad SAW was born at dawn precisely on the 12th of Rabi’ul Awal. The existence of dikia is very difficult to find because fans of badikia in the millennial era are very minimal. Badikia players have stepped on the elderly which makes it difficult for the next generation to understand more about the structure of badikia. The Covid-19 pandemic also became an obstacle to badikia performances because it allegedly invited crowds. Concerns about the existence of Dikia Pauah will be lost because the younger generation as the successor of many do not understand the presentation of Dikia Pauah in a structured manner.